SYSTEMIC PREREQUISITES FOR SHAPING THE LOCAL BUDGETS’ TAX REVENUE: THE CASE STUDY OF DEVELOPED COUNTRIES - Iryna Storonyanska; Khrystyna Patytska; Tetiana Medynska; Liliya Benovska; Liliia Kliuchnyk; Olha Nestor (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The study aims to determine the systemic prerequisites for shaping the local budgets’ tax revenue and analyze its impact on the development of municipalities in developed countries. The authors examine the impact of the following factors on the municipal budgets’ tax revenue: the behavioural patterns of economic entities (in particular, in terms of property management), the role of the state in shaping the municipal budgets’ tax revenue, and the comprehension of the nature of the tax. Using the example of defining the economic nature of personal income tax, the article proves (based on the analysis of municipal budgets’ tax revenue in EU countries) that the policy of local governments regarding the accumulation of the tax for their budgets changes as the essential characteristics of the tax change. Based on a comparison of the experience of municipalities in developed countries, the authors identify the factors influencing property taxation systems that shape property tax revenue: differences in the structure of the economy and the effects of its change, behavioural reactions of economic entities and existing traditions of property ownership in different countries, peculiarities of the property market development in various countries, etc. Trends in the structure of the economy and their potential impact on the tax capacity of local budgets are analyzed. The need for diversification of tax revenue sources to provide municipalities with an adequate level of resilience in the face of constant economic changes and permanent crises is emphasized.